Basic principles of lasers. Issue 3 (March 2021) - Haley, Daniel
Abstract: The theoretical basis for laser was first described by Einstein, over 100 years ago. Lasers are now in widespread use and have an extensive range of applications, including many within the field of medicine. This article explores the properties of laser its physical principles and the main components required to produce a laser beam. The specific properties of laser, render it an extremely useful clinical tool in a variety of circumstances. The application of laser also brings potential hazards, which are discussed, along with the safety measures utilized to minimize the associated risk.